2022
DOI: 10.1007/s11325-022-02594-2
|View full text |Cite
|
Sign up to set email alerts
|

Ertugliflozin and incident obstructive sleep apnea: an analysis from the VERTIS CV trial

Abstract: Purpose The sodium-glucose transporter 2 inhibitor (SGLT2i) empagliflozin may reduce the incidence of obstructive sleep apnea (OSA) in patients with type 2 diabetes (T2D) and cardiovascular (CV) disease. This analysis of VERTIS CV, the CV outcome trial for the SGLT2i ertugliflozin conducted in a similar group of patients, explored the effects of ertugliflozin on reported incident OSA. Methods In VERTIS CV, patients ≥ 40 years with T2D and atherosclerotic C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…SGLT2i have been shown to reduce incident obstructive sleep apnea in two SGLT2i CVOTs based on adverse event reporting (304,305). However, it is not clear that the data collected on incident obstructive sleep apnea in these trials were complete or that the benefit is mediated through changes in weight.…”
Section: Obesity and Weight-related Comorbidities Particularly Nafld ...mentioning
confidence: 99%
“…SGLT2i have been shown to reduce incident obstructive sleep apnea in two SGLT2i CVOTs based on adverse event reporting (304,305). However, it is not clear that the data collected on incident obstructive sleep apnea in these trials were complete or that the benefit is mediated through changes in weight.…”
Section: Obesity and Weight-related Comorbidities Particularly Nafld ...mentioning
confidence: 99%
“…An exploratory analysis showed that approximately 7% of the population enrolled experienced baseline OSA. Among patients without baseline OSA, there was a 48% reduction for incident OSA in those treated with ERTU versus placebo (p = 0.04) [102]. There was an early differentiation in the incidence of OSA (from the first 12 months of the study) between patients treated with ERTU versus placebo.…”
Section: Ertugliflozinmentioning
confidence: 89%
“…For instance, the SURMOUNT-OSA (NCT05412004) study, a 52-week, phase III randomised controlled trial, is underway to explore the efficacy and safety of tirzepatide (a GLP-2 and GIP receptor agonist) in the treatment of OSA. Similarly, sodium-glucose co-transporter-2 inhibitors (SGLT2is), a group of medications that has been shown to offer major cardio and renoprotective effects in recent trials, have also demonstrated encouraging results in OSA [ 142 , 143 , 144 ]. Putative mechanisms include weight reduction, reduced systemic fluid retention, nocturia-mediated suppression for the duration of REM sleep, suppression of circadian SNS activation, reduced CO 2 production and modulation of arousal threshold [ 145 , 146 , 147 , 148 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%